2022
DOI: 10.1177/19476035221126343
|View full text |Cite
|
Sign up to set email alerts
|

Minced Autologous Chondral Fragments with Fibrin Glue as a Simple Promising One-Step Cartilage Repair Procedure: A Clinical and MRI Study at 12-Month Follow-Up

Abstract: Objective The aim of this study was to investigate early radiological and clinical outcome of autologous minced cartilage treatment as a single-step treatment option in patients with a chondral or osteochondral lesion (OCL) in the knee. Design Eighteen patients with an OCL in the knee were included. Cartilage from healthy-appearing loose bodies and/or the periphery of the defect were minced into small chips and sealed in the defect using fibrin glue. Preoperatively, and at 3 ( n = 14) and 12 ( n = 18) months f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 85 publications
0
12
0
1
Order By: Relevance
“…Even if the method was proven safe, the product is currently unavailable for clinical use. Three other clinical studies have shown promising results with improved clinical and radiological (MOCART) scores [ 5 , 16 , 25 ]. The clinical relevance of the present study becomes clear when the clinical studies are looked in detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if the method was proven safe, the product is currently unavailable for clinical use. Three other clinical studies have shown promising results with improved clinical and radiological (MOCART) scores [ 5 , 16 , 25 ]. The clinical relevance of the present study becomes clear when the clinical studies are looked in detail.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was not until two decades later that further studies on animal models were published [ 8 , 14 ]. Finally, the first clinical studies have been published, showing promising results in outcome scores [ 5 , 16 , 25 ]. Medical companies have recognized the potential of this method and are investing in standardized products such as shavers or cartilage harvesting devices.…”
Section: Introductionmentioning
confidence: 99%
“…Second, microfracture/microdrilling may not have been effective enough to overcome the existing degenerative changes in the knee. Although patients included in this study showed good cartilage restoration with a mean MOCART score of 65 [24, 39], it is assumed that the effect of such cartilage restoration did not last long. In fact, the mid‐to‐long‐term effects of MSP are known to be relatively limited [10].…”
Section: Discussionmentioning
confidence: 99%
“…This pericellular matrix plays an important role in preserving joint homeostasis [ 10 , 11 ]. The initial clinical studies show a promising outcome of MCI at up to 2 years of follow-up [ 12 , 13 , 14 ] with limited evidence. Cartilage repair is performed in a majority (60%) of degenerative, non-traumatic defects (data from the German Society for Orthopaedics and Trauma cartilage registry) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%